Quality of life in patients with obstructive sleep apnea: Relationship with daytime sleepiness, sleep quality, depression, and apnea severity. (February 2016) - Lee, Wonhee; Lee, Sang-Ahm; Ryu, Han Uk; Chung, Yoo-Sam; Kim, Woo Sung
The aim of this study was to investigate the relative contributions of daytime sleepiness, sleep quality, depression, and apnea severity to mental and physical quality of life (QoL) in obstructive sleep apnea (OSA) patients. This was a cross-sectional study. Participants were adults diagnosed with OSA. Medical Outcomes Study–Short Form 36 (SF-36), Epworth Sleepiness Scale (ESS), Medical Outcomes Study–Sleep Scale, and Beck Depression Inventory (BDI) were used. The factors predicting the physical and mental QoL were evaluated using multiple linear regression analysis. Seven hundred ninety three OSA patients participated in the study. The average age was 48.9 years ( SD = 11.7 years). The mean apnea–hypopnea index (AHI) was 29.5 hour −1 ( SD = 20.6 hour −1 ). The SF-36 scores were 72.6 ( SD = 18.5). The BDI, sleep quality, and age were related to both mental and physical QoL. However, ESS, minimal arterial oxygen saturation, gender, and body mass index were associated with the physical but not mental QoL. The BDI was the strongest predictor of both physical and mental QoL. AHI was related to neither physical nor mental QoL. The potential factors affecting QoL are different between physical and mental dimensions of QoL. Depressive mood was the strongest predictor of both the physical and mental QoL.